The impact of ultrasonic cavitation on the chemical transformations of model compounds - Baikenov, M.I.; Tateyeva, A.B.; Matayeva, A.Zh.; Balabekova, D.A.; Yessebayev, B.O.; Tleubergenova, A.B.; Berzhanova, R.S. (Изд-во КарГУ, 2013)
The effect of ultrasonic cavitation on various organic compounds in the presence of catalysts is investigated in order to identify the chemistry of reactions. In addition, practical applications of cavitation for cracking hydrocarbons in technological processes of oil-refining industry are considered and estimated. These findings indicate that the use of cavitation for destruction of organic compounds is effective for technological and economical aspects.
Keywords: ultrasonic cavitation; destruction; isomerization of hydrocarbons; chemical transformation of model compounds